Veleposjedi u Slavoniji nakon Drugog svjetskog rata - Gardaš, Miro; Repić, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In the first decades of the 20th century, in the area of ​​Slavonia there were several large estates that belonged to noble families and operated under their administration, or parts of such estates were leased to business entities that used them. Some large estates covered huge areas of forest and agricultural land and yielded large incomes. There were also a number of smaller economic entities that significantly contributed to the economic prosperity of Slavonia. After World War II, all these estates were taken away from the previous owners and transferred to state ownership. In this process, court proceedings were conducted in which, among other penalties, the penalty of confiscation of all property was obligatorily imposed. The main guilt of the owners of these economic entities was the alleged cooperation with the enemy, although they actually only carried out their regular economic activity during the Second World War. On the examples of individual Slavonian noble families, we will try to show how this procedure took place in everyday court practice. Thanks to that, in the first decades of the 20th century, Osijek grew into a strong economic center in which some of the most important business entities operated. In the archive sources stored in the State Archives in Osijek, we can find documents in several archival funds that provide us with an insight into the court proceedings that were conducted after the Second World War. We can see from the court proceedings that the property was confiscated from individuals and their families who held high positions in the regime of the Independent State of Croatia and cooperated with the German army. However, the property was also confiscated from many families whose only crime was that during the war their factories, workshops, and agricultural estates regularly performed their daily activities. The archival material used in writing this paper is primarily contained in the following archival funds: The District Court of Osijek, The County Court of Osijek, Court for the Protection of the National Honor of Croats and Serbs in Croatia. Gaps in the court proceedings materials were filled with data from other archival funds stored in the State Archives in Osijek. It is particularly interesting that lawsuits for "cooperation with the occupier" were filed not only against Germans and Croats who owned large estates, factories, or crafts but also against Serbs and Jews whose factories and crafts continued to operate during World War II. It is ironic that proceedings for "cooperation with the occupier" were also conducted against Jews who were taken to concentration camps during the war in which they disappeared. Their factories and crafts were nationalized by the Independent State of Croatia authorities and sold to other persons or given to the commissioners for management. However, as the authorities after the Second World War did not recognize any deals or contracts concluded at the time of the Independent State of Croatia, they filed charges for "cooperation with the occupier" against the previous owners, who were imprisoned or killed by those authorities. In each of these proceedings, in addition to other penalties, a penalty of confiscation of complete property was imposed. Sentences ranged from death and imprisonment to an almost negligible number of sentences of the loss of national honor or short-time suspended sentences that were always combined with the penalty of the confiscation of all property that in some cases was very large. This archival material was especially topical when the return of confiscated property began in Croatia.